Danshensu methyl ester enhances autophagy to attenuate pulmonary fibrosis by targeting lncIAPF–HuR complex - Zhu, Qi; Wang, Jing; Ji, Yunxia; Luan, Jianlin; Yue, Dayong; Liu, Weili; Li, Hongbo; Zhang, Jinjin; Qu, Guiwu; Lv, Changjun; Song, Xiaodong (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis is an irreversible fibrotic process that has a high mortality rate and limited treatment options; thus, developing a novel therapeutic drug is critical. In this study, we synthesized danshensu methyl ester (DME) and explored its anti-pulmonary fibrotic ability on TGF-β1-stimulated lung fibroblast in vitro and on bleomycin-induced pulmonary fibrosis in vivo. Results showed that DME decreased the expression of differentiation-related proteins, including fibroblast activation protein 1 (FAP1) and S100 calcium-binding protein A4 (S100A4), and fibrotic markers, such as α-SMA, vimentin, and collagen in vivo and in vitro. In addition, DME markedly repressed myofibroblast proliferation and migration. Mechanistically, chromatin immunoprecipitation–PCR, RNA immunoprecipitation, half-life, and other experiments revealed that DME inhibited activating transcription factor 3 expression via TGF-β1 signal transduction leading to a decrease in lncIAPF transcription and stability. Moreover, DME blocked human antigen R (HuR) nucleocytoplasmic translocation and promoted its degradation via downregulating lncIAPF, which markedly decreased the expression of HuR target genes such as negative autophagic regulators (EZH2, STAT1, and FOXK1). Collectively, our results demonstrated that DME enhanced autophagy to attenuate pulmonary fibrosis via downregulating the lncIAPF–HuR-mediated autophagic axis and the lncIAPF–HuR complex can be the target for drug action.